DOMESTIC ARBITRATION LAW FOR ALTERNATIVE RESOLUTION OF DISPUTES PERFORMANCE IMPROVEMENT PROSPECTS - Abdumurad Abdusaidovich Khakberdiev (PT. Antis International Publisher, 2025)
Objective: The study examines the ongoing reforms in the law enforcement and judicial-legal systems of our country, particularly focusing on the role of Domestic Arbitration Law in safeguarding human rights, freedoms, and legitimate interests. It aims to explore ways to improve the application of Domestic Arbitration Law in resolving civil and economic disputes through alternative dispute resolution mechanisms. Method: The research employs a qualitative approach, analyzing legal frameworks and case studies to evaluate the effectiveness of current Domestic Arbitration practices. It also investigates the challenges faced by arbitration bodies in handling disputes and explores comparative insights from other jurisdictions. Results: The findings reveal that despite gradual legal reforms and the increasing involvement of competent courts, Domestic Arbitration Law still encounters significant obstacles. These include inconsistencies in legal provisions, limited public awareness, and procedural inefficiencies, which hinder its effectiveness in resolving disputes. Novelty: This study contributes to the discourse on alternative dispute resolution by providing actionable recommendations for enhancing Domestic Arbitration Law. It emphasizes the need for comprehensive legal reforms and awareness campaigns to establish arbitration as a viable and efficient alternative to traditional court proceedings.